2013
DOI: 10.1074/jbc.m112.435289
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antigen Recognition Mode of a Shark Immunoglobulin New Antigen Receptor (IgNAR) Variable Domain Characterized by Humanization and Structural Analysis

Abstract: Background: Single domain variable regions of shark antibodies (V-NARs) are promising biotherapeutic candidates. Results: A V-NAR specific for human serum albumin was humanized, and its crystal structure in complex with the antigen was solved, revealing an unusual recognition mode. Conclusion: Humanization preserved antigen binding properties and activity of the parental shark antibody. Significance: A structural framework for humanization of shark antibodies was established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(106 citation statements)
references
References 36 publications
3
103
0
Order By: Relevance
“…Structurally, VNAR domains have a classic immunoglobulin fold and superimposition of human variable heavy and light chains onto VNAR domains, revealed a structural relatedness within the core framework [34]. However this remarkable example of structural convergent evolution, is where the similarity ends as sequence comparison reveals only 25%-30% identity to mammalian heavy chains.…”
Section: To Be or Not To Be An Antibodymentioning
confidence: 99%
See 2 more Smart Citations
“…Structurally, VNAR domains have a classic immunoglobulin fold and superimposition of human variable heavy and light chains onto VNAR domains, revealed a structural relatedness within the core framework [34]. However this remarkable example of structural convergent evolution, is where the similarity ends as sequence comparison reveals only 25%-30% identity to mammalian heavy chains.…”
Section: To Be or Not To Be An Antibodymentioning
confidence: 99%
“…VNARs however are not limited to binding into canyons or clefts. Kovalenko and colleagues crystallized a Type IIb domain that was raised against HSA in a spiny dogfish [31,34]. This domain lacks the non-canonical CDR-framework cysteine and resultantly has a more flexible structure.…”
Section: Small Size But Large Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Dimer and trimer constructs can be expressed and purified and still exhibit functionality [51]. They are also amenable to re-formatting as Fc if the cell killing function and half-life extension is required [66]. Size, affinity and tissue penetration are correlated and in a cancer tissue penetration model, provided a high-enough affinity is achieved, the advantages of a smaller proteinbinding domain will be realised [67].…”
Section: Drug Developmentmentioning
confidence: 99%
“…This study highlighted some key hallmark residues within VNAR isotypes across different species and has illustrated the tolerance of these domains for alterations within the sequence and retention of function, informing possible sites for conjugation and humanisation. A recent publication by Kovalenko et al [66], focussing on an anti-human serum albumin (HSA) VNAR domain isolated from an immunised dogfish [51] showed that humanisation is achievable without loss of function. The question of the need to humanise has yet to be answered in vivo but the humanised versions of these VNAR domains show negligible antigenicity in human dendritic cell assays (personal communication).…”
Section: Drug Discoverymentioning
confidence: 99%